The Influence Of Product, Service, And Wom On Customer Loyalty: Purchasing Decisions As An Intervening Variable At Waroeng Kampoeng 99 - Dwi Danesty Deccasari Danesty; Maulana Hanif Abbyan; Marli (LP2M IAIN Palopo, 2025)
This study aims to examine the influence of product quality, customer service, and word-of-mouth (WOM) recommendations on consumer loyalty, considering the mediating role of purchasing decisions at Waroeng Kampoeng. The approach used is quantitative with a comparative design, involving 100 respondents, of which 99 are regular customers. Data collection was carried out using a Likert-based questionnaire instrument, while data analysis used the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with a bootstrapping procedure of 5,000 samples. Model validity and reliability testing were carried out using composite reliability indicators, Average Variance Extracted (AVE), and outer loading, all of which met the established acceptance threshold. The research findings indicate that purchasing decisions have a significant influence on consumer loyalty (β = 0.485; p < 0.001). Customer service was proven to have a significant influence on purchasing decisions (β = 0.235; p = 0.020), although it did not have a direct impact on loyalty. Product quality showed a significant influence on consumer loyalty (β = 0.300; p = 0.019) and purchasing decisions (β = 0.253; p = 0.037). In contrast, WOM did not show a significant mediating effect on loyalty (β = 0.123; p = 0.067). This finding implies the importance of strategic planning that focuses on improving product quality and service quality as an effort to strengthen customer loyalty in the food and beverage (F&B) sector. Although WOM did not show significance in this study, its potential to provide long-term impact remains an area worthy of exploration. Further research is recommended by expanding the sample size and adding moderating variables, such as price sensitivity.